Nonthermal plasma processing for nanostructured biomaterials and tissue engineering scaffolds: A mini review. (March 2021) - Tucker, Bernabe S.; Aliakbarshirazi, Sheida; Vijayan, Vineeth M.; Thukkaram, Monica; De Geyter, Nathalie; Thomas, Vinoy
Abstract: Traditional wet chemistry offers a great magnitude of methods for surface modification and surface coatings for nanostructured materials. However, most methods require solvents and purification steps, and generate waste and byproducts. An interesting alternative set of methods involves the use of nonthermal or low-temperature plasmas (LTP) toward making and modifying nanostructured biomaterials. In this current opinion piece, some of the recent literature in this area is highlighted, and current perspectives are given. Emphasis is noted for the role of LTP for surface modification of nanofibrous scaffolds and plasma electrolytic oxidation (PEO) for surface-nanostructuring of metallic implants. The morphological nanofeaturing in fibrous mats as an extracellular matrix mimicking scaffold is presented along with recent perspectives of using LTP and plasma electrolytic oxidation for surface structuring for enhanced biointegration via cell/surface interactions with plasma processed implants/scaffolds constructs.